Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1590/s1676-06032006000100022
|View full text |Cite
|
Sign up to set email alerts
|

Estrutura de comunidades de aves em áreas de cerrado da região nordeste do Estado de São Paulo

Abstract: Concerning that the cerrado region is one

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…), citrus plantations, pastures and roads such as the SP-253 highway. There are 211 bird species recorded for the area (Almeida 2002);…”
Section: Methodsmentioning
confidence: 99%
“…), citrus plantations, pastures and roads such as the SP-253 highway. There are 211 bird species recorded for the area (Almeida 2002);…”
Section: Methodsmentioning
confidence: 99%
“…Nos últimos 30 anos alguns trabalhos sobre a avifauna das matas semidecíduas foram realizados no interior do Estado de São Paulo (Willis, 1979;Willis & Oniki, 1981, 2002Motta Junior, 1990;Vielliard & Silva, 1990;Aleixo & Vielliard, 1995;Almeida et al, 1999;Chiarello, 2000;Almeida, 2002;Pozza & Pires, 2003;Donatelli et al, 2004Donatelli et al, , 2007Antunes, 2005), e o conhecimento de algumas localidades é bastante compreendido. No entanto, a Estação Ecológica dos Caetetus, considerada área prioritária para a conservação de aves, e de alta importância biológica no que diz respeito a endemismo, riqueza e graus de conservação e ameaça das aves da Mata Atlântica (MMA, 2000), ainda não possui dados suficientes sobre a composição da comunidade de suas aves.…”
Section: Introductionunclassified
“…The main part of studies about Cerrado bird communities that we found did not address the relationship between bird diversity and vegetation structure and physiognomy directly (Motta Jr., 1990;Lins, 1994;Antas, 1999;Abreu, 2000;Curcino et al, 2007;Braz, 2008;Sendoda, 2009;Tolesano-Pascoli et al, 2010;Cavarzere, 2013;Pascoal et al, 2013). Other studies were focused in descriptions of bird diversity in diverse and undersampled regions (Almeida, 2002;Pacheco and Olmos, 2006;Martins, 2007;Costa and Rodrigues, 2012;Olmos and Brito, 2007) and few ones had investigated quantitatively the relation of bird diversity with physiognomy in a local scale. (Tubelis and Cavalcanti, 2001;Silva, 2004;Piratelli and Blake, 2006;Rodrigues and Faria, 2007;Motta-Junior et al, 2008;Valadão, 2012;Posso et al, 2013;Fieker, 2012).…”
Section: Discussionmentioning
confidence: 99%